Subway shield synchronous grouting material capable of fully replacing recycled sand and preparation method of subway shield synchronous grouting material
By using a full alternative to the grouting material prepared with other materials, the ecological environment and engineering cost brought by the use of fine aggregate in the traditional grouting material in the traditional grouting material, and realized the efficient resource utilization of the residual mud of engineering residue. Excellent performance of grouting.
Patent Information
- Application Number
- CN202411475081.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
AI Technical Summary
The fine aggregates used in traditional grouting materials mainly come from natural sand or high-quality quartz sand, which leads to ecological and environmental protection problems and high engineering costs, and the residual mud of engineering waste has not been reasonably utilized, resulting in waste of resources and environmental pollution.
The raw material that uses full alternative recycling sand as grouting materials, and mixes with the sand with cement, coal ash, silica ash, polycar carboxylic acid water reduction and water recovered by the engineering residue. The mixer is stirred to prepare grouting materials with excellent flow and high -solidity rate.
The efficient resource utilization of engineering residue mud is realized, reducing the dependence on natural sand and quartz sand, reducing the cost of engineering, protecting the environment, and meeting the liquidity and intensity requirements of shields.
Smart Images

Figure BDA0005095860340000041 
Figure BDA0005095860340000051 
Figure BDA0005095860340000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of shield slurry, and specifically relates to a fully-replacement and recovery sand subway shield synchronous grouting material and a preparation method thereof. Background Art
[0002] Shield construction is one of the key technologies in subway tunnel construction. During the advancement of the shield machine, an annular gap with a width of about 115 to 140 mm will be formed between the segment and the soil. If this gap is not filled in time, the soil around the segment may loosen or even collapse, leading to serious consequences such as surface subsidence. Therefore, it is very important to use grouting to fill the gap in the shield tail building in time. In addition, backing grouting can also improve the water-stopping performance of the tunnel, evenly distribute the external force on the segment, and ensure the early stability of the segment lining.
[0003] Cement-based grouting material is a mortar made of high-strength granular materials as fine aggregates, cement and other materials as cementing materials, and admixtures. Fine aggregate accounts for up to 50% of the weight of grouting materials, and its demand is huge. However, the fine aggregate used in traditional grouting materials mainly comes from natural sand or high-quality quartz sand. In order to protect the ecological environment, the mining of natural sand is restricted, and high-quality quartz sand is expensive, which has prompted the engineering community to seek alternatives to reduce the use of these materials in order to reduce engineering costs and reduce the consumption of natural sand resources.
[0004] With the development of rail transit, a large amount of slag and mud has been generated. The traditional way to dispose of engineering slag and mud is to transport them to landfills for stacking. Not only is the transportation distance long and the cost high, but the stacking occupies a large amount of land resources, and may also cause environmental pollution and geological safety accidents. According to relevant data, my country currently discharges more than 2 billion tons of engineering waste mud and slag every year, accounting for more than 60% of the total construction waste. According to statistics, the slag and mud generated by my country's subway projects has rapidly increased from 160,000 cubic meters in 1965 to 68.82 million cubic meters in 2018, and is expected to exceed 200 million cubic meters by 2030. However, most of the slag and mud have not been reasonably and effectively utilized. The main components of slag and mud are sand and gravel and mud. Among them, sand and gravel is one of the main building materials required for current engineering construction. In 2023, the national supply and demand of sand and gravel will be as high as 16.835 billion tons. Therefore, the development of efficient resource utilization technology for engineering slag and mud, turning waste into treasure, has a strong practical engineering demand and has important economic and social environmental effects. Summary of the invention
[0005] In response to the above-mentioned existing technical problems, the present invention provides a fully-replacement recycled sand subway shield synchronous grouting material and a preparation method thereof. The grouting material has excellent fluidity, moderate initial setting time, high consolidation rate, and the initial strength and final strength meet the design requirements.
[0006] In a first aspect, the present invention provides a fully-replacement recycled sand subway shield synchronous grouting material, wherein the raw material composition of the grouting material includes recycled sand, cement, fly ash, silica fume, a water reducer and water.
[0007] Furthermore, the raw material composition of the grouting material includes 1450-1500 parts of recycled sand, 120-130 parts of cement, 320-360 parts of fly ash, 50-80 parts of silica fume, 0.5-1 part of water reducing agent and 390-410 parts of water, calculated by weight.
[0008] Furthermore, the cement is silicate cement, and the P·II grade is not less than 42.5R.
[0009] Furthermore, the fly ash is Class II fly ash.
[0010] Furthermore, the silica fume grade is not less than SF92.
[0011] Furthermore, the water reducer is a polycarboxylate water reducer.
[0012] Furthermore, the recovered sand is sand recovered from engineering slag, and the recovered sand is medium sand with a mud content of 5.3%, a fineness modulus Mx=2.8, and a loose bulk density of 1520kg / m 3 , compact packing density 1660kg / m 3 , the particle size distribution of washed sand belongs to zone 2;
[0013] The recovery of sand from construction waste soil is divided into two methods: dry screening and water washing, according to the type of waste soil and its moisture content. For waste soil with low moisture content and good soil particle dispersion, the dry screening method is used to recover sand. The steps include:
[0014] 1) Coarsely screen the slag to remove organic impurities, isolated stones and other large stones;
[0015] 2) The excavated soil is naturally air-dried to reduce the moisture content to below 15%;
[0016] 3) Mechanically crush and disperse the soil particles;
[0017] 4) Use a drum dryer to dry the slag;
[0018] 5) Use a roller mill to roll the dried slag for 10 to 15 minutes;
[0019] 6) The slag after wheel rolling is screened, and the upper limit of the sieve hole diameter is 4.75mm and the lower limit is 0.075mm. The screened material within this range is the recovered sand.
[0020] For slag with high moisture content and serious agglomeration, water washing method is used to recover sand, the steps include:
[0021] 1) Coarsely screen the slag to remove organic impurities, isolated stones and other large stones;
[0022] 2) Use impeller sand washing machine to wash the slag;
[0023] 3) After washing, the material is dehydrated and screened to obtain recovered sand.
[0024] In the second aspect, the present invention provides a method for preparing a fully-replacement recycled sand subway shield synchronous grouting material, the steps comprising: mixing the raw materials according to mass fractions, then stirring with a planetary cement mortar mixer, and stirring for 360s to 420s according to a fixed procedure to obtain a fully-replacement recycled sand subway shield synchronous grouting, and packaging the grouting material with a moisture-proof bag.
[0025] Furthermore, the fixed procedure is:
[0026] 1) Mix cement, fly ash, silica fume, water reducer and water for the first stirring for 1 to 2 minutes;
[0027] 2) Adding recovered sand to the above mixture and stirring for a second time for 4 to 6 minutes to obtain a grouting material.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The shield grouting material of the present invention adopts wet-process produced recycled sand as raw material. The recycled sand comes from the slag mud of rail transit, which reduces the use of natural sand or quartz sand. It can turn waste into treasure, realize the efficient and high value-added resource utilization of engineering slag mud, and solve the problems faced by the current traditional disposal methods of large-scale construction solid waste slag mud, such as high cost, occupation of land resources, environmental pollution and high risk of geological disasters. It can also save materials, reduce the consumption of natural resources and protect the environment. At the same time, it can also reduce costs and increase efficiency. The fully-replacement recycled sand subway shield synchronous grouting material of the present invention has good environmental and socio-economic benefits.
[0030] (2) The fully-replacement sand recovery subway shield synchronous grouting material of the present invention adopts a combination of polycarboxylic acid water-reducing agent, fly ash, silica fume and other materials to improve the fluidity and stability of the grouting material. The slurry meets the fluidity requirements and has a consolidation rate of ≥95% while maintaining high fluidity, which can meet the grouting requirements for different purposes.
[0031] (3) The initial setting time of the fully replaced recycled sand metro shield synchronous grouting material of the present invention is between 3 and 10 hours, which can provide higher early strength.
[0032] (4) This grouting material has excellent fluidity, moderate initial setting time, high consolidation rate, and the initial strength and final strength meet the design requirements. The 1d compressive strength is ≥0.2MPa and the 28d compressive strength is ≥2.5MPa.
[0033] (5) The shield grouting material of the present invention uses recycled sand as raw material. The recycled sand comes from the slag and mud of rail transit, which reduces the consumption of natural sand or quartz sand. It can not only realize the efficient and high value-added resource utilization of engineering slag and mud, but also reduce the consumption of natural resources and reduce costs. It has good environmental and socio-economic benefits. DETAILED DESCRIPTION
[0034] The experimental methods in the following examples of the present invention, where no specific conditions are specified, are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.
[0035] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0036] The terms "including" and "having" and any variations thereof of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, device, product or equipment comprising a series of steps is not limited to the listed steps or modules, but may optionally include steps not listed, or may optionally include other steps inherent to these processes, methods, products or equipment.
[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0038] The present invention is further described in the following examples, but the examples are not intended to limit the scope of protection of the present invention.
[0039] The raw materials and sources not specifically mentioned in the specific implementation mode of the present invention are all the same product:
[0040] The cement used was P·Ⅱ42.5R silicate cement produced by China Resources Cement (Pingnan) Co., Ltd.; the fly ash used was Class C Ⅱ fly ash produced by Wushigang Co., Ltd. in Qujiang District, Shaoguan City; the silica fume used was provided by Guangdong Gatechi New Materials Technology Co., Ltd.; the water reducer used was Sika polycarboxylate water reducer 325C, powder;
[0041] Recycled sand (mud content 5.3%, fineness modulus Mx = 2.8, loose bulk density 1520kg / m 3 , compact packing density 1660kg / m 3 , the sand particle size distribution belongs to zone 2) is sand recovered from engineering slag by water washing. The specific preparation method is:
[0042] 1) Coarsely screen the slag to remove organic impurities, isolated stones and other large stones;
[0043] 2) Use an impeller sand washer to wash the slag, and control the washing time according to the mud content of the slag, so that the surface of the sand at the discharge port is relatively clean and has no obvious mud marks;
[0044] 3) The washed sand is drum-dehydrated or naturally dehydrated so that there is no obvious water seepage when the dehydrated sand is piled up;
[0045] 4) Dry the sand naturally or in a drum until it is well dispersed and free of adhesion and agglomeration;
[0046] 5) Two-stage screening is adopted, specifically using a vibrating screen machine, the aperture distribution of the two-stage screens is 4.75mm and 0.15mm, and the middle section (particle size 4.75-0.15mm) of sand is obtained, which is the recovered sand.
[0047] Example 1 Preparation of Synchronous Grouting Material for Subway Shield Tunneling with Fully Replaced Recycled Sand
[0048] The composition of the fully replaced recovered sand metro shield synchronous grouting material of the present embodiment is as follows:
[0049]
[0050] The recovered sand has a mud content of 5.3%, a fineness modulus Mx=2.8, and a loose bulk density of 1520 kg / m 3 , compact packing density 1660kg / m 3 , the particle grading of washed sand belongs to zone 2.
[0051] The preparation steps of the fully replaced recycled sand metro shield synchronous grouting material of this embodiment are as follows:
[0052] Mix cement, fly ash, silica fume, water reducer and water according to their mass proportions, stir them for the first time for 1 to 2 minutes, then add recycled sand to the mixture and stir it for the second time for 4 to 6 minutes to obtain fully replaced recycled sand subway shield synchronous grouting material, and finally package the grouting material with a moisture-proof bag.
[0053] Example 2 Preparation of Synchronous Grouting Material for Subway Shield Tunneling with Fully Replaced Recycled Sand
[0054] The composition of the fully replaced recovered sand metro shield synchronous grouting material of the present embodiment is as follows:
[0055]
[0056] The recovered sand has a mud content of 5.3%, a fineness modulus Mx=2.8, and a loose bulk density of 1520 kg / m 3 , compact packing density 1660kg / m 3 , the particle grading of washed sand belongs to zone 2.
[0057] The preparation steps of the fully replaced recycled sand metro shield synchronous grouting material of this embodiment are as follows:
[0058] Mix cement, fly ash, silica fume, water reducer and water according to their mass proportions, stir them for the first time for 1 to 2 minutes, then add recycled sand to the mixture and stir it for the second time for 4 to 6 minutes to obtain fully replaced recycled sand subway shield synchronous grouting material, and finally package the grouting material with a moisture-proof bag.
[0059] Example 3 Preparation of Synchronous Grouting Material for Subway Shield Tunneling with Fully Replaced Recycled Sand
[0060] The composition of the fully replaced recovered sand metro shield synchronous grouting material of the present embodiment is as follows:
[0061]
[0062] The recovered sand has a mud content of 5.3%, a fineness modulus Mx=2.8, and a loose bulk density of 1520 kg / m 3 , compact packing density 1660kg / m 3 , the particle grading of washed sand belongs to zone 2.
[0063] The preparation steps of the fully replaced recycled sand metro shield synchronous grouting material of this embodiment are as follows:
[0064] Mix cement, fly ash, silica fume, water reducer and water according to their mass proportions, stir them for the first time for 1 to 2 minutes, then add recycled sand to the mixture and stir it for the second time for 4 to 6 minutes to obtain fully replaced recycled sand subway shield synchronous grouting material, and finally package the grouting material with a moisture-proof bag.
[0065] Test Example 1: Performance test of fully replacing recycled sand subway shield synchronous grouting material
[0066] Part I. Test methods
[0067] The fully substituted recycled sand metro shield synchronous grouting material prepared in Examples 1 to 3 was subjected to performance tests, and the specific test indicators and methods are as follows:
[0068] (1) Initial setting time test: refer to GB / T 1346-2011 "Test methods for water consumption, setting time and stability of cement of standard consistency";
[0069] (2) Consolidation strength test: refer to the standard JGJ / T70-2009 "Standard for test methods of basic properties of building mortar";
[0070] (3) Consolidation rate test: refer to DB11 / T 1608-2018 "Technical Specifications for Application of Premixed Shield Grouting Materials";
[0071] (4) Truncated cone fluidity test: refer to GB / T 50448-2015 "Technical Specifications for Application of Cement-based Grouting Materials";
[0072] Part II: Performance Test Results
[0073] According to the test method in the first part, the performance test results are shown in Table 1;
[0074] Table 1: Performance test results of fully replaced recycled sand metro shield synchronous grouting materials prepared in Examples 1 to 3
[0075]
[0076] It can be seen from the performance test results in Table 1 that the initial setting time of the fully replaced recycled sand subway shield synchronous grouting material prepared by recycled sand in Examples 1 to 3 of the present invention is between 3 and 10 hours, which can provide higher early strength and good consolidation strength. The 1d compressive strength is ≥0.2MPa, and the 28d compressive strength is ≥2.5MPa, which meets the main physical and mechanical performance requirements of the synchronous grouting slurry; the present invention improves the fluidity and stability of the grouting material by adopting specific polycarboxylic acid water reducer, fly ash, silica fume and other materials in combination with recycled sand. The slurry meets the fluidity requirements, and the consolidation rate is ≥95% while maintaining high fluidity, which can meet the grouting requirements for different purposes.
[0077] Comparative Example 1
[0078] The difference between this comparative example and Example 2 is that no water reducing agent is used, and the remaining ingredients and contents, as well as the preparation method are consistent with those of Example 2.
[0079] Comparative Example 2
[0080] The difference between this comparative example and Example 2 is that no water reducing agent is used, and an equal amount of cellulose ether is used to adjust the fluidity. The other components and contents, as well as the preparation method are consistent with those in Example 2.
[0081] Comparative Example 3
[0082] The difference between this comparative example and Example 2 is that the raw material composition content of the fully replaced recycled sand subway shield synchronous grouting material is different, as shown in Table 2:
[0083] Table 2: Raw material composition of fully replaced recycled sand subway shield synchronous grouting material
[0084]
[0085] The sand recovery subway shield synchronous grouting material is prepared by fully replacing the raw material composition in Table 2, and the preparation method is consistent with Example 2.
[0086] Comparative Example 4
[0087] The difference between this comparative example and Example 2 is that the recovered sand is different. The recovered sand used in this comparative example has a mud content of 8.36%, a fineness modulus Mx=2.49, and a loose bulk density of 1252.5 kg / m 3 , compact packing density 1488.6kg / m 3 The particle size distribution of the washed sand belongs to zone 2, and the other components and contents, as well as the preparation method are consistent with those in Example 2.
[0088] The method for preparing the recovered sand in this comparative example is basically the same as that in Example 2, except that the sieve aperture in step 5) is different and is adjusted according to the actual needs of the recovered sand.
[0089] Comparative Example 5
[0090] The difference between this comparative example and Example 2 is that the recovered sand is different. The recovered sand used in this comparative example has a mud content of 2.1%, a fineness modulus Mx=3.5, and a loose bulk density of 1355kg / m 3 , compact packing density 1527kg / m 3 The particle size distribution of the washed sand belongs to zone 3, and the other components and contents, as well as the preparation method are consistent with those in Example 2.
[0091] The method for preparing the recovered sand in this comparative example is basically the same as that in Example 2, except that the sieve aperture in step 5) is different and is adjusted according to the actual needs of the recovered sand.
[0092] Test Example 2: Performance Test of Synchronous Grouting Material for Metro Shield
[0093] The performance test of the subway shield synchronous grouting materials prepared in Comparative Examples 1 to 5 was carried out. The specific test indicators and methods were consistent with those of Test Example 2. The experimental results are shown in Table 3:
[0094] Table 3: Performance test results of fully replaced recycled sand subway shield synchronous grouting materials prepared in comparative examples 1 to 5
[0095]
[0096] It can be seen from the performance test results in Table 3 that the subway shield synchronous grouting materials prepared in Comparative Examples 1 to 5 have poorer performance than Examples 1 to 3. The main reason is that no water reducer is added in Comparative Example 1, resulting in a truncated cone fluidity lower than the requirement; Comparative Example 2 uses an equal amount of cellulose ether instead of a water reducer. Although the fluidity meets the requirement, the initial setting time is longer than the requirement; Comparative Example 3 uses a low content of recovered sand and a consolidation rate lower than the requirement; the recovered sand of Comparative Example 4 has a large mud content of 8.36% and a low consolidation strength; the particle size distribution of the recovered sand of Comparative Example 5 belongs to zone 3 coarse sand and has a low fluidity.
[0097] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A fully-replacement recycled sand subway shield synchronous grouting material, characterized in that: Calculated by weight, the raw material composition of the grouting material includes 1450-1500 parts of recycled sand, 120-130 parts of cement, 320-360 parts of fly ash, 50-80 parts of silica fume, 0.5-1 part of water reducer and 390-410 parts of water.
2. The fully-replacement recovery sand metro shield synchronous grouting material according to claim 1 is characterized in that: The recovered sand is medium sand with a mud content of 5.3% and a fineness modulus Mx=2.
8.
3. The fully-replacement recovery sand metro shield synchronous grouting material according to claim 1 is characterized in that: The cement is silicate, and the cement grade is not less than 42.5R.
4. The fully-replacement recovery sand metro shield synchronous grouting material according to claim 1 is characterized in that: The loose bulk density of the recovered sand is 1520 kg / m 3 , compact packing density 1660kg / m 3 , the particle grading of washed sand belongs to zone 2.
5. The fully-replacement recovery sand metro shield synchronous grouting material according to claim 1 is characterized in that: The fly ash is Class II fly ash.
6. The fully-replacement recovery sand metro shield synchronous grouting material according to claim 1 is characterized in that: The silica fume grade is not less than SF 92.
7. The fully-replacement recovery sand metro shield synchronous grouting material according to claim 1 is characterized in that: The water reducer is a polycarboxylate water reducer.
8. The fully-replacement recovery sand metro shield synchronous grouting material according to claim 1 is characterized in that: The recovered sand is sand recovered from engineering slag, and the steps include: 1) Coarsely screen the slag to remove organic impurities, isolated stones and other large stones; 2) Dry drying and crushing or wet washing; 3) Finally, the material is dehydrated and screened to obtain recycled sand.
9. A method for preparing the fully-replacement and recovery sand-recovery synchronous grouting material for subway shield tunneling according to any one of claims 1 to 8, characterized in that: The preparation steps include: mixing the raw materials according to mass fractions, and then stirring for 360s to 420s according to a fixed procedure to obtain a fully-replacement recycled sand subway shield synchronous grouting material.
10. The method for preparing the fully-replacement and recovery sand-recovery subway shield synchronous grouting material according to claim 9, characterized in that: The fixed procedure is: 1) Mix cement, fly ash, silica fume, water reducer and water for the first stirring for 1 to 2 minutes; 2) Adding recovered sand to the above mixture and stirring for a second time for 4 to 6 minutes to obtain a grouting material.